European exceptionalism? - Nolte, Georg 1959-; Aust, Helmut Philipp 1980- (Discussion paper, 2012)
The paper discusses recent propositions that forms of a "European exceptionalism" are now emerging. The paper first asks what makes a political entity "exceptionalist". For this purpose inspiration is sought in "American exceptionalism" as a model. The paper then discusses whether "Europe" displays comparable features in the fields of international legal policy and domestic rights culture. It also asks whether there are other aspects of European governance which could make it plausible to speak of a European exceptionalism. The paper concludes that it is misleading to use the term "European exceptionalism" because the underlying phenomena are not comparable what is usually understood as "American exceptionalism". -- European exceptionalism ; exceptionalist ; American exceptionalism